C(sp 3 )–H cyclizations of 2-(2-vinyl)phenoxy- tert -anilines - Dunkel, Petra; Bogdán, Dóra; Deme, Ruth; Zimber, Ádám; Ballayová, Veronika; Csizmadia, Eszter; Kontra, Bence; Kalydi, Eszter; Bényei, Attila; Mátyus, Péter; Mucsi, Zoltán (RSC advances, 2024)
1,5-hydride transfer-triggered cyclization reactions offering a robust method for C(sp 3 )–C(sp 3 ) coupling and the synthesis of e.g. tetrahydroquinolines have been thoroughly investigated in the literature. Catalysts allowing milder reaction conditions or the development of enantioselective processes were important recent contributions to the field, as well as the studies on subtrates with oxygen or sulfur heteroatoms (besides the originally described nitrogen heterocycles). In a series of studies, we focused on expanded, higher order H-transfers/cyclizations by positioning the interacting substituents on distanced rings. Cyclizations of appropriately functionalized biaryl and fused bicyclic systems led to 7–9 membered rings. In the frame of this research, we set out to study the feasibility of the cyclization and the factors affecting it by in silico methods. The conclusions drawn from computational studies were complemented by cyclization screens on 2-(2-vinyl)phenoxy- tert -anilines and their CH 2 -expanded analogues, the results of which are presented here. Besides isolating the expected oxazonine products in several cases, we also observed a unique dimer formation, leading to an interesting 5-6-5 ring system.